General features, types, techniques, benefits, safety and adverse effects related to Pranayamas mentioned in traditional Hatha Yoga texts: A review on Pranayama chapters - Dipak Chetry; Prerna; Dilip Kumar Rajak; Archana Chhetri (Wolters Kluwer Medknow Publications, 2022)
Pranayama is one of the most important and widely practiced components of Hatha Yoga. Among the traditional Hatha Yoga texts, the Hatha Yoga Pradipika (HYP) and Gheranda Samhita (GS) (written between 1200 A.D. and 1857 A.D.) are the two most influential and practical foundational texts on Pranayama, which are very useful even till date. Previously published reviews on Hatha Yoga texts only cover the brief overview, concept of Kundalini, concept of Pranayamas, and comparative study on Asanas. The present study was conducted to systematically review: (1) the general features of Pranayama practices, (2) types and techniques of Pranayama practices, (3) the benefits of Pranayama practices, and (4) safety and adverse effects related to Pranayama practices mentioned in HYP and GS. The original verses written in Sanskrit were translated into English for correct interpretation of the general features, types, techniques, benefits, safety, and adverse effects related to Pranayama as mentioned in the two Hatha Yoga texts. In this review, the verses on Pranayama are systematically reviewed, arranged, and presented under the four mentioned points.